PERBANDINGAN KANDUNGAN ASAM SINAMAT DAN ASAM BENZOAT DALAM KEMENYAN (Styrax benzoin) KUALITAS I,III DAN V YANG DIPEROLEH DARI DAERAH TAPANULI UTARA DENGAN METODE KROMATOGRAFI GAS - Fatma Suryani Harahap; Harlem Marpaung (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
AbstractA research has been done about the comparation of the cinnamic acid and benzoic acid content in the frankincenses (Styrax benzoin) quality I, III and V which of obtained from Pangaribuan region (North Tapanuli). The cinnamic acid and benzoic acid content are analyzed by using Gas Chromatography with injection volume 1 µl. The data is analyzed qualitatively by measuring the retention time standard solution, with cinnamic acid and benzoic acid content are determained by using calibration curve with linier regretion from least square method. The result show the cinnamic acid and benzoic acid from the frankincenses class I is 26, 4303 %, and 3,3573 %, frankincenses class III is 26,0270%  and 2,0705%, frankincenses class V is 0,2884% and 1,5916%.Keywords : Frankincenses, cinnamic acid, benzoic acid, Gas Chromatography